Digital Literacy Analysis of Elementary School Students Through Implementation of E-Learning Based Learning Management System - Dewi, Candra (Universitas Pendidikan Ganesha, 2022)
The COVID-19 pandemic that has hit the world has resulted in changes in all aspects of life, including the education aspect. Initially, education was held face-to-face, due to the COVID-19 pandemic, face-to-face learning began to be limited. Face-to-face learning is replaced with online learning (e-learning) based on a learning management system (LMS) so that students are expected to still be able to learn even from home. The implementation of e-learning in the teaching and learning process in schools requires digital literacy competencies. Through e-learning students can access various information on the internet so that digital literacy skills are one solution in responding to the challenges of technological advances. This study aims to analyze the digital literacy skills of elementary school students through the application of LMS-based e-learning. This research is a descriptive analysis. The subjects in this study were fifth grade elementary school students who applied LMS-based e-learning as many as 25 students. While the data collection methods used are surveys and interviews. Data analysis methods used include data collection, data reduction, data presentation, and decision making. The results showed that there were three aspects, most of the students had sufficient digital literacy skills and there were four aspects where most of the students had good abilities. So it can be concluded that the students' digital literacy abilities are mostly in the sufficient and good category. Thus, e-learning can have an impact on students' digital literacy skills.